2016
DOI: 10.1016/j.intfin.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity risk contagion in the interbank market

Abstract: This paper studies liquidity risk contagion within the interbank market by assessing the long-run relationship of short-term interest rate spreads from January 2002 to December 2015. In particular, we model the interaction between the LIBOR-OIS spread, euro fixed-float OIS swap rate and the threemonth US-German bond spread and discover strong evidence of structural innovations affecting the interbank market. We find that when the short-term interbank market is affected by a liquidity shock, the LIBOR-OIS sprea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 52 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…Diamond and Rajan (2011) show that banks might become illiquidity seekers to avoid realized losses due to asset fire sales and in anticipation of asset price recoveries. Eross et al (2016) find evidence of endogenous responses and spillovers within the interbank market. Lopez-Espinosa et al…”
Section: Related Literaturementioning
confidence: 83%
“…Diamond and Rajan (2011) show that banks might become illiquidity seekers to avoid realized losses due to asset fire sales and in anticipation of asset price recoveries. Eross et al (2016) find evidence of endogenous responses and spillovers within the interbank market. Lopez-Espinosa et al…”
Section: Related Literaturementioning
confidence: 83%
“…When faced with underlying risks, banks have a serious sense of panic, which will be transmitted to the major institution of neighboring banks through the credit association network under the influence of the irrational behavior of the bank. en, the neighboring bank conveys a sense of panic to the neighboring bank, finally showing a remarkable "herd mentality" [12,58,59].…”
Section: Credit Risk Contagion Probability Of Bank Networkmentioning
confidence: 99%
“…The conclusion derived when they assessed how the concentration of credit relationships and the position of a bank in the network topology of the system influence the bank's ability to meet liquidity demand using quarterly data of bilateral interbank credit exposure among all Germany banks from 2000 to 2008 to measure interbank relationships and network characteristics. Eross et al (2016) study liquidity risk contagion within the interbank market by assessing the long-run relationship of short-term interest rate spreads from January 2002 to December 2015. They found that when the short-term interbank market is affected by a liquidity shock, the London Interbank Offered Rate-overnight index swap spread is a leader in moving back to equilibrium, while the euro-dollar currency swap rate and the USA-German bond spreads are followers.…”
Section: Literature Reviewmentioning
confidence: 99%